Tajam Penglihatan Pra Dan Pasca Operasi Pars Plana Vitrektomi Pada Pasien Ablasio Retina Di Rumah Sakit Pertamina Bintang Amin Bandar Lampung - Rahmat Syuhada; Ade Utia Detty; Mizar Erianto; Rizal Kamaludin Hidayat (Malahayati Nursing Journal, 2021)
ABSTRACT: PRE AND POST OPERATION OF VITRECTOMIC PARS PLANE FOR ABLASIO RETINA PATIENTS AT PERTAMINA HOSPITAL BINTANG AMIN BANDAR LAMPUNG Background :Retinal detachment is a condition in which the sensory parts of the retina (photoreceptors and deep tissue layers) and the retinal pigment epithelium (RPE) are separated (Budhiastra, 2016). the world, which is 1 in 10,000 population. And the average age of 40-70 years is the most susceptible to retinal detachment. This prevalence can increase if the patient with retinal detachment has several other conditions such as aphaxia / pseudophakia, high myopia and trauma. in young people they are more likely to experience retinal detachment caused by trauma, and in people aged 25-45 years, retinal detachment is more common due to high myopia. Purpose: The purpose of this study was to determine the sharp vision of pre and post pars plana vitrectomy patients with retinal detachment at Pertamina Bintang Amin Hospital in Bandar Lampung in 2020. Result : The results of 60 respondents with visual acuity from retinal detachment patients who successfully increased were 47 respondents with a percentage (78.3%) and 13 respondents with retinal detachment who did not improve were 13 respondents with a percentage (21.7%) and retinal detachment patients with retinal detachments were found. As many as 49 respondents managed to attach with a percentage (81.7%) for retinal detachment patients whose retina failed to adhere, 11 respondents (18.3%) were found. Conclusion : There is a significant difference between pre and post-operative Pars Plana Vitrectomy in patients with retinal detachment Keywords: Retinal Detachment, Pars Plana Vitrectomy, Sharp Eyesight  INTISARI  : TAJAM PENGLIHATAN PRA DAN PASCA OPERASI PARS PLANA VITREKTOMI PADA PASIEN ABLASIO RETINA DI RUMAH SAKIT PERTAMINA BINTANG AMIN BANDAR LAMPUNG TAHUN 2020 Pendahuluan: Ablasio retina adalah keadaan dimana bagian sensoris retina (fotoreseptor dan lapisan jaringan dalam) dan retinal pigment epithelium (RPE) menjadi terpisah (Budhiastra, 2016) Ablasi retina bisa diartikan juga  terpisahnya sel kerucut dan batang retina dari sel epitel pigmen retina, Prevalensi ablasio retina di dunia yaitu sebanyak 1 berbanding 10.000 populasi. Dan rata-rata usia 40-70 tahun adalah yang paling rentan terkena ablasio retina. Prevalensi tersebut bisa meningkat jika penderita ablasio retina tersebut memiliki beberapa keadaan lain  seperti afaksia/pseudofakia, myopi tinggi dan trauma. pada orang muda  mereka lebih sering mengalami ablasio retina yang disebabkan oleh trauma, serta pada orang berusia usia 25-45 tahun ablasio retina lebih sering terjadi dikarenakan myopia tinggi.Tujuan : Tujuan dari penelitian ini adalah untuk mengetahui Tajam Penglihatan pasien ablasio retina pra dan pasca operasi pars plana vitrektomi di Rumah sakit Pertamina Bintang Amin Bandar Lampung tahun 2020.Hasil : Hasil dari 60 responden tajam penglihatan dari pasien ablasio retina yang berhasil meningkat didapatkan responden sebanyak 47 orang dengan persentase (78.3%) dan tajam penglihatan pasien ablasio retina yang tidak meningkat didapatkan sebanyak 13 reponden dengan persentase (21.7%) dan didapatkan pasien ablasio retina yang retina berhasil menempel sebanyak 49 responden dengan persentase (81.7%) untuk pasien ablasio retina yang retina gagal menempel didapatkan responden sebanyak 11 dengan persentase (18.3%). Kesimpulan : Terdapat perbedaan yang cukup signifikan dari tajam penglihatan pra dan pasca Operasi Pars Plana Vitrektomi pada pasien Ablasio Retina Kata kunci    :  Ablasio Retina, Pars Plana Vitrektomi, Tajam Penglihatan